Clinical and functional outcomes of revision hip replacement surgeries - Aditya K. Agrawal; Malay Gandhi; Mohit Jain; Sarvang Desai; Paresh Golwala (Journal of Orthopaedic Reports, 2024)
Background: Hip replacement surgeries are common operations done in throughout the world since last five decades. The change and refinement in technology along with surgical skills have improved the outcomes in hip hemiarthroplasties, total hip arthroplasties and revision hip arthroplasties. The aim of this study is to present the clinical and functional outcomes of patients admitted for revision hip replacement surgeries at a tertiary care hospital. Materials and Method: After receiving the IEC (Institutional Ethics Committee) approval, patients admitted at our hospital for revision total hip arthroplasty were enrolled in our study. Results were analyzed using SPSS software (Illinois, Chicago) and p value of <0.01 was considered statistically significant. Results: We present here a case series of ten patients (six males and four females) who underwent surgery for revision hip arthroplasty. Mean age of the patients was found to be 55.7 ± 16.3 years (average age in females was 61.75 ± 7.2 years, average age in males was 43.2 ± 15.4 years). Index surgery was done 15.3 ± 4.6 years. Patient related outcome measures measured by Oxford Hip Score were found to improve at final follow up which was statistically significant. Conclusion: All necessary blood and radiological investigations are required to reach to a diagnosis along with meticulous pre-operative planning after proper consent with due documentation. Check all necessary implants and instruments in the armamentarium. Postoperative rehabilitation protocol has to be gradual with emphasis on high protein and vitamin intake. It requires adequate surgical training and experience along with out of the box lateral thinking.